2022
DOI: 10.1007/jhep10(2022)078
|View full text |Cite
|
Sign up to set email alerts
|

Giant gravitons, Harish-Chandra integrals, and BPS states in symplectic and orthogonal $$ \mathcal{N} $$ = 4 SYM

Abstract: We find generating functions for half BPS correlators in $$ \mathcal{N} $$ N = 4 SYM theories with gauge groups Sp(2N), SO(2N + 1), and SO(2N) by computing the norms of a class of BPS coherent states. These coherent states are built from operators involving Harish-Chandra integrals. Such operators have an interpretation as localized giant gravitons in the bulk of anti-de-Sitter space. This extends the analysis of [1] to Sp(2N), SO(2N + 1), and SO(2N) gauge theories. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This would explain why certain angular momentum modes are allowed on the spin chain description, even though semiclassically they are forbidden by the boundary conditions. Our calculation in the gauge theory demonstrate the power of the methods introduced in [22,30,31] for computing correlators of fully-symmetric Schur polynomials. Our methods are in many respects more streamlined when compared to the approach introduced in [4] for dealing with symmetric Schur functions.…”
Section: Jhep05(2023)167mentioning
confidence: 69%
“…This would explain why certain angular momentum modes are allowed on the spin chain description, even though semiclassically they are forbidden by the boundary conditions. Our calculation in the gauge theory demonstrate the power of the methods introduced in [22,30,31] for computing correlators of fully-symmetric Schur polynomials. Our methods are in many respects more streamlined when compared to the approach introduced in [4] for dealing with symmetric Schur functions.…”
Section: Jhep05(2023)167mentioning
confidence: 69%
“…Similar integrals have been constructed for the projectors onto representations labelled by a single column or row, with an arbitrary length [53,54]. Another development [55][56][57][58], which is closely related, has shown that many of the results from the combinatorial approach can be reproduced by writing suitable generating functions of coherent states as a matrix integral. In some cases these matrix integrals are related to the well known Harish-Chandra-Itzykson-Zuber integral and can be computed using localization.…”
Section: Jhep01(2023)104mentioning
confidence: 83%
“…More recently, there have been works showing that certain generating functions can be used to perform computations in the free-field theory limit [8][9][10][11][12]. This technique has been succesfully implemented in the computation of three-point correlators involving large operators made out of a single matrix field [13][14][15], as in the half-BPS sector of N = SYM [16,17], where the dual gravitational description is explicitly realized from the gauge theory.…”
Section: Introductionmentioning
confidence: 99%